2013
DOI: 10.1016/j.pain.2013.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a reduced dose of an intrathecal local anesthetic with a small dose of an opioid: A meta-analysis of randomized trials

Abstract: a b s t r a c tWe tested whether the combination of a reduced dose of a local anesthetic (LA) with an opioid compared with a standard dose of the same LA alone guaranteed adequate intraoperative anesthesia and postoperative analgesia and decreased LA-related adverse effects. We systematically searched (to November 2012) for randomized comparisons of combinations of a reduced dose of an LA with a concomitant opioid (experimental) with a standard dose of the LA alone (control) in adults undergoing surgery with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…The incidence of pruritus in nonobstetric surgery patients after intrathecal morphine ranges from 15% to 70% 32-34 and after intrathecal fentanyl or sufentanil, from 53% to 79%. [23][24][25]29 A meta-analysis of 28 trials by Pöpping et al 9 demonstrated that intrathecal fentanyl and sufentanil allowed for a lower dose of intrathecal local anesthetic and hastening recovery from motor block but at the price of an increased risk of pruritus (RR, 11.8; 95% CI, 6.2-21.9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pruritus in nonobstetric surgery patients after intrathecal morphine ranges from 15% to 70% 32-34 and after intrathecal fentanyl or sufentanil, from 53% to 79%. [23][24][25]29 A meta-analysis of 28 trials by Pöpping et al 9 demonstrated that intrathecal fentanyl and sufentanil allowed for a lower dose of intrathecal local anesthetic and hastening recovery from motor block but at the price of an increased risk of pruritus (RR, 11.8; 95% CI, 6.2-21.9).…”
Section: Discussionmentioning
confidence: 99%
“…1-4 Moreover, adding an opioid to neuraxial blockade reduces local anesthetic dose, which limits hemodynamic consequences and shortens recovery time. [5][6][7][8][9] Given increasing demand for effective, low-dose neuraxial techniques, selection of intrathecal opioid has been the topic of several recent studies. [10][11][12][13] Fentanyl and sufentanil are lipophilic opioids with similar chemical structure and intrathecal pharmacokinetics.…”
mentioning
confidence: 99%
“…In addition, PCEA has the advantages of small dosage, reliable analgesic effect, long duration, limited range of action and relatively small systemic effects, which can be used for postoperative analgesia, cancer carbuncle of chest, abdomen and lower extremity and traumatic pain (multiple rib fractures, pelvic fractures) [20,21]. Especially, the combined use of local anesthetic and opioid analgesics, also called balanced analgesia method, can reduce the doses of each drug and reduce the side effects of drugs, which can effectively inhibit metabolic and endocrine responses resulting from nociceptive stimulation [22,23]. Some previous studies have revealed that after some thoracic and gynecological operations, PCEA presented more merits in postoperative analgesia than PCIA and could effectively relieve pain both on coughing and at rest [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…33 The balanced analgesia method uses opioid analgesics as additives with local anesthetic to reduce the dosage and lower the side effects of individual drugs, efficiently preventing endocrine stress responses and adverse physiological responses from noxious stimulation. 34,35 In this study, we also compared the patients' clinical data, and our results revealed that patients in the PCEA group had shorter surgery time and duration of anesthesia compared with patients in the PCIA group. VAS scores, a measure of the degree of pain, were significantly lower in the PCEA group in comparison with the PCIA group at 3, 6, 12, 24, and 48 hours after spinal fusion surgery.…”
Section: Discussionmentioning
confidence: 90%